Poinfekcyjna nadreaktywność oskrzeli w praktyce lekarza pierwszego kontaktu. Czy istnieją wskazania do leczenia? - Bokiej, Juliusz; Jurdyga, Małgorzata; Fic, Mirosław (Przewodnik Lekarza/Guide for GPs, 2010)
Bronchial hyperreactivity as a feature or functional condition of bronchi is well defined. It\'s described as the increased tendency to contraction reaction of bronchi as a response to various immunological and non-immunological stimuli exposure [1]. Due to its presence in various clinical conditions it\'s not helpful in differential diagnosis of respiratory system diseases. In some cases (5-10-14%) it can be find as a congenital dysfunction at healthy individual [2, 3]. Patient with prolonged, recurrent whistling sounds in airways or with chronic cough are often treated as a “post-infection bronchial hyperreactivity” or diagnosed further as asthma cases. In spite of many treatment problems, there are no guidelines for bronchial hyperreactivity therapy. It seems that treatment taking depends on clinical experience of physician and should regard his criticism and differential diagnosis.